Fe–Mn–Ga shape memory glass-coated microwire with sensing possibilities. (26th October 2021) - Galdun, L; Vidyasagar, R; Hennel, M; Varga, M; Ryba, T; Nulandaya, L; Milkovič, O; Reiffers, M; Kravčák, J; Vargova, Z; Varga, R
Abstract: The structural phase transformation in a non-stoichiometric shape memory Fe42.8 Mn27.6 Ga29.6 Heusler glass-coated microwire was experimentally observed using indirect magnetic, permeability, and electrical resistance measurements. While the temperature dependence of magnetization revealed hysteresis of magnetization during the heating and cooling process, magnetic hysteresis loops point to the change in the direction of the easy magnetization axis of the low- and high-temperature phase. Additionally, the unusual behavior of the permeability and electrical resistance measurements are in good agreement with the magnetic measurements. The x-ray diffraction profile measured at room temperature revealed the coexistence of a high-temperature L21 phase ( a = 5.88 Å) and low-temperature phase with the L12 structure ( a = 3.71 Å) and can be considered as another proof of the shape memory effect that is expected in the Fe–Mn–Ga-based Heusler alloys. In the presented glass-coated microwire, it is not only possible to shift the transformation temperature with the external magnetic field, but from its initial permeability value, it is possible to determine whether the alloy has undergone the structural transformation. Therefore, the presented Fe–Mn–Ga-based glass-coated microwire may be considered a suitable candidate for microactuators with sensory capabilities.